Analisis Pandangan Hakim Terhadap Cerai Murtad Perspektif Hukum Islam di Pengadilan Agama Kraksaan Probolinggo Jawa Timur - Muhammad Rizky Maulana; Fathullah Rusly; Abd. Hannan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research examines the judge’s views on apostate divorce cases from the perspective of Islamic law at the Kraksaan Religious Court, Probolinggo, East Java. The research method used was descriptive qualitative with snowball sampling technique for sampling. Primary data was obtained from documentation and direct interviews with judges at the Kraksaan Religious Court, while secondary data came from books, laws and related journals. The results of the analysis show that the judge’s views on apostate divorce are influenced by various factors, including religious, legal, social, economic and humanitarian aspects. The judge carefully considers the reasons for apostate divorce in accordance with the provisions of Islamic law and applicable positive law. The judge’s decision in an apostate divorce case must take into account the welfare of the child, socio-cultural conditions, the couple’s economic capabilities, and the principles of justice. This research underscores the importance of judges’ decision making that is fair and balanced, taking into account all relevant factors to reach a dignified solution for all parties involved in the divorce process.